An interval robust design optimization method and its application in heat transfer problems. Issue 10 (3rd October 2021) - Tian, W. Y.; Sun, W. T.; Ni, B. Y.; Li, J. W.; Wu, Z. T.
ABSTRACT: An interval robust optimization method is suggested to improve the robustness and performance of the process or product in design. A general uncertain robust optimization problem is considered in which the objective function and constraints are both nonlinear and uncertain, and the uncertainties of design variables and uncertain parameters are all included and depicted by the interval model. A nonlinear interval number programming method is introduced to solve the robust optimization model, in which the uncertain objective function is described by a pair of deterministic functions, and the uncertain constraints are converted to deterministic constraints on the basis of the reliability-based possibility degree of interval. The method is then applied to several heat transfer problems for performance optimization of the heat transfer processes while guaranteeing the robustness of the optimal design.